Establishing the places of care for the old people in The Diaries of Jane Somers by Doris Lessing - Arikan, Seda (Elsevier Science Inc, 2022)
The Nobel-prize winner Doris Lessing brings forward the significance of caring for the old and dying people in her novel The Diaries of Jane Somers, which reveals that human flourishing is based on responsibility, interde-pendency, and trust between the carer and cared for. In this novel, Lessing mainly emphasizes the significance of caring for both close relatives and distant others who suffer from old age and sickness via the protagonist Jane Somers, who develops unconditional care for a ninety-year-old woman, Maudie Fowler. By depicting Jane's transformation into a caring and interdependent character, contrary to her earlier indifference and autonomy, Lessing proposes that the claims of the old, the sick, and the dying people could be responded to by sharing their experiences and feelings, especially in their personal places. In this respect, this study aims to explore the relationship between literature and care ethics within the scope of ageing studies. This study will embrace the claims of care ethicists and analyse how they are reflected in a literary work. Thus, the aim is to create awareness through literature about caring for older, sick, and dying people by establishing or sharing the places of care, such as older people's homes, rooms, beds, bathrooms, and even deathbeds.
Keywords: Doris Lessing; The Diaries of Jane Somers; Places of care; Ethics of care; Ageing